Social Enterprise Challenges: Case Study (Global Business Management Review (GBMR), 2022)
Social enterprises are income-generating businesses balancing its objectives of social and business concerns. It doesn’t matter whether the organisation is profit oriented or non-profit oriented. The goal of social enterprise needs to incorporate these two goals: to achieve social, cultural, community commercial or conservation outcomes; and, to earn income. Contextualising the topic to Surabaya Zoo in Indonesia, a short case study has been conducted to explore the issues in relation to the social enterprise concept. It has been observed that the Zoo is facing many management issues in relation to the social enterprise concept. A qualitative approach that follows content analysis of secondary data is used to arrive at projecting the observations and developing an alternative conceptual model that to make the operation of the zoo effective.